2018
DOI: 10.1016/j.cherd.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of hydrodynamic cavitation with orifice: Influence of different orifice designs

Abstract: Hydrodynamic cavitation (HC) may be harnessed to intensify a range of industrial processes, and orifice devices are one of the most widely used for HC. Despite the wide spread use, the influence of various design and operating parameters on generated cavitation is not yet adequately understood. This paper presents results of computational investigation into cavitation in different orifice designs over a range of operating conditions. Key geometric parameters like orifice thickness, hole inlet sharpness and wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 29 publications
0
54
0
2
Order By: Relevance
“…The analytical process follows mass conservation, kinetic energy conservation, and the continuity equation. On this basis, the κ − ε turbulence model, the Euler model, and the Rayleigh equation considering cavitation change are used [15].…”
Section: Basic Mathematical Modelmentioning
confidence: 99%
“…The analytical process follows mass conservation, kinetic energy conservation, and the continuity equation. On this basis, the κ − ε turbulence model, the Euler model, and the Rayleigh equation considering cavitation change are used [15].…”
Section: Basic Mathematical Modelmentioning
confidence: 99%
“…Designs of cavitation reactor: Conventionally hydrodynamic cavitation reactors are designed either using small constrictions (like orifices or venturi) or rotors to realise the desired low pressure regions for generating cavitation. Orifice or venturi based designs are susceptible to clogging and erosion since cavitation occurs close to solid walls (see for example, Simpson and Ranade, 2018a). Reactors based on rotors are expensive and impose higher operating and maintenance costs (Gogate and Pandit, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore difficult to relate results of one study with the other since these devices lack standardisation. It should be noted that small hardware features like thickness of orifice plate and radius of curvature of orifice (see Simpson and Ranade, 2018a) can significantly influence cavitation characteristics. Many times, not all of the relevant dimensions and operating conditions (like cavitation inception conditions, volume of holding tank etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The formulation and numerical solution of multiphase computational fluid dynamics (CFD) models have recently been used to evaluate geometric parameters of orifice devices used for hydrodynamic cavitation . Cavitation behaviours were drastically affected by the orifice thickness (ie, length of the hole).…”
Section: Generation Of Micro‐nanobubblesmentioning
confidence: 99%
“…For example, for the ratio of orifice thickness to diameter from 1‐5, the pressure ratio required to initiate cavitation changed by a factor of 10. The analysis revealed that all the geometric parameters (such as inlet radius, hole inlet sharpness, and wall angle) affect cavitation intensity …”
Section: Generation Of Micro‐nanobubblesmentioning
confidence: 99%